Effects of structed drill practice on the precision of overhead clears: a quasi-experiential research study in collegiate badminton players - Fariz Maulana Syawshindra; Eval Edmizal; Donie Donie; Juanda Putra (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
This study investigated the effect of structured drill training on the accuracy of overhead clear shots among badminton athletes at the UNP Badminton Academy, Padang, Indonesia. The research was motivated by the athletes’ inconsistent overhead clear performance, which contributed to the academy’s inability to reach the top eight in the 2024 UNP Rector Cup despite serving as the tournament host. A quantitative quasi-experimental approach with a one-group pretest–posttest design was employed. Twelve athletes were selected through purposive sampling from a population of 24 registered academy athletes. Overhead clear accuracy was assessed using the French Test, a standardized instrument with documented validity (0.60) and high reliability (0.98), administered before and after 16 sessions of structured drill training. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and a paired-sample *t*-test at a significance level of α = .05. The results showed a substantial improvement in overhead clear accuracy following the intervention. The mean score increased from 59.33 (SD = 16.12) at the pretest to 84.33 (SD = 6.95) at the posttest. Both datasets met the normality assumption, and the paired-sample *t*-test revealed a statistically significant difference between pretest and posttest scores (*t*(10) = −6.240, *p* < .001). These findings suggest that structured, repetition-based drill training is effective in enhancing overhead clear shot accuracy among competitive badminton athletes. However, because the study employed a single-group design without a control group, alternative explanations such as maturation, testing, or history effects cannot be entirely ruled out. Nevertheless, the findings provide preliminary empirical evidence supporting the use of structured drill training as an effective approach for improving technical performance in badminton and offer practical implications for coaches in designing skill development programs.